A Closer Look at the Social Entrepreneurship Ecosystem in Latvia: Opportunities for Building Performance (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2023)
Social entrepreneurship in Latvia is steadily attracting the attention of policymakers, researchers, and the wider public. The expectations are high, but so is the need to strategically continue developing the field. One road towards strengthening the performance and overall social impact is critically evaluating the effectiveness of the social entrepreneurship ecosystem. Nascent research has been scarce and dominated by qualitative studies. Therefore, based on quantitative survey analysis, this study aims to contribute to the extant knowledge by offering valuable insights into the social entrepreneurship ecosystem in Latvia, highlighting the strengths and weaknesses and the relationships closely associated with enhanced social enterprise performance. Research results indicate significant potential for developing cooperation with different public sector organisations and confirm the critical role of incubators/accelerators, finance providers, support organisations and social enterprise community in furthering the sector's overall performance.